2021
DOI: 10.3390/ijms22115439
|View full text |Cite
|
Sign up to set email alerts
|

Structural Perspectives on the Mechanism of Soluble Guanylate Cyclase Activation

Abstract: The enzyme soluble guanylate cyclase (sGC) is the prototypical nitric oxide (NO) receptor in humans and other higher eukaryotes and is responsible for transducing the initial NO signal to the secondary messenger cyclic guanosine monophosphate (cGMP). Generation of cGMP in turn leads to diverse physiological effects in the cardiopulmonary, vascular, and neurological systems. Given these important downstream effects, sGC has been biochemically characterized in great detail in the four decades since its discovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 74 publications
1
18
0
Order By: Relevance
“…Conventional sGC activation proceeds through NO binding to a ferrous heme located within the sGCβ subunit of a mature sGC α–β heterodimer ( 13 , 14 ). This causes protein structural changes that activate cGMP production ( 13 16 ). The essential role that heme plays in sensing NO underscores the importance of the heme delivery and insertion steps that enable sGC to mature in cells ( 17 ).…”
mentioning
confidence: 99%
“…Conventional sGC activation proceeds through NO binding to a ferrous heme located within the sGCβ subunit of a mature sGC α–β heterodimer ( 13 , 14 ). This causes protein structural changes that activate cGMP production ( 13 16 ). The essential role that heme plays in sensing NO underscores the importance of the heme delivery and insertion steps that enable sGC to mature in cells ( 17 ).…”
mentioning
confidence: 99%
“…The 3-D structure of the sGC β-subunit H-NOX domain is remarkably well-conserved among species, while the amino acids of the H-NOX cavity which mediate the interaction of H-NOX with heme are remarkably well-conserved between bacterial and mammalian species (e.g. Nostoc punctiforme, Bos taurus ), being identical by ∼63% (17 of 27, ( Alexandropoulos et al., 2016 ; Makrynitsa et al., 2019 ; Wittenborn and Marletta, 2021 ). This is why rational drug design based on microbial H-NOX structural data and on the very structure of heme has contributed to, and still informs, the development of sGC activator molecules all the way to advanced clinical trials (reviewed in Alexandropoulos et al., 2016 ; Makrynitsa et al., 2019 ; Liu et al., 2021 ; Wittenborn and Marletta, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nostoc punctiforme, Bos taurus ), being identical by ∼63% (17 of 27, ( Alexandropoulos et al., 2016 ; Makrynitsa et al., 2019 ; Wittenborn and Marletta, 2021 ). This is why rational drug design based on microbial H-NOX structural data and on the very structure of heme has contributed to, and still informs, the development of sGC activator molecules all the way to advanced clinical trials (reviewed in Alexandropoulos et al., 2016 ; Makrynitsa et al., 2019 ; Liu et al., 2021 ; Wittenborn and Marletta, 2021 ). Despite all this, it is understood that ideally, any conclusions derived from a structural approach using a recombinant microbial domain (in this case Nostoc sp.…”
Section: Resultsmentioning
confidence: 99%
“…In the review by Wittenborn et al the current view of full length sGC revealed by novel structures obtained by cryo-electron microscopy is summarized. The authors discussed the inactivated and activated states of the enzyme to describe the detailed biochemical mechanism and its function, which could be helpful to elucidate new sGC modulators for pharmacological treatments [ 6 ].…”
Section: Communicationmentioning
confidence: 99%